PERANCANGAN ILUSTRASI DONGENG SI KANCIL DAN SI KERA UNTUK ANAK USIA 4-6 TAHUN - Citra Kemala Putri, Dwi Agustini Indriani (ArtComm, 2018)
The Fabel Story of Kancil in Indonesia generally contains a fictional story that has bad image so it is poorly delivered for early childhood. For example, TKQ student Miftahul Hidayah is familiar with the story of Kancil which has bad character, such as deceiving Crocodile to get across the river, and more familiar about The Story of Kancil through foreign-made television shows than fairy tales in Indonesian-made print media. Researchers use qualitative and quantitative methods in processing this phenomenon. Data collection techniques were conducted by interview, observation, literature study and questionnaire. This design is made for children of early age generally, and especially students TKQ Miftahul Hidayah which is more familiar with the typical Indonesian story of Kancil that came along with illustrations and narratives that are appropriate to children. So that it can educate the moral of the children through the story of the Kancil which has changed its view into the better character of Kancil. Keywords: tale, Kancil, early childhood, illustration, narrative